Evolution of photodynamic therapy in the management of actinic keratosis: how effective and safe is it according to current evidence? Evolución de la terapia fotodinámica en el manejo de la queratosis actínica ¿qué tan efectiva y segura es según la evidencia actual? - Vargas-Monroy, Laura Valentina (2024)
Actinic keratosis is a premalignant dermatological condition characterized by the potential to progress to squamous cell carcinoma. To date, there is no treatment with an adequate benefit-risk balance. Photodynamic therapy is proposed as one of the most effective therapeutic tools. However, there is still divergence regarding the quality of available evidence. The objective of this review is to analyze the most recent evidence on the therapeutic performance of photodynamic therapy in the management of actinic keratosis. A literature search was conducted in the PubMed, Scopus, and MEDLINE databases. Based on the most recent randomized controlled trial comparing the use of dynamic phototherapy combined with aminolevulinic acid without incubation versus incubation for one hour, it was found that the intervention group had a higher percentage of lesion resolution compared to the control group (49.5% vs. 34.9%, p=0.002), as well as less pain in the intervention group (p=0.03). In addition, a similar trend was observed in other studies, suggesting that this therapy could be effective and beneficial in the management of actinic keratosis. Despite the limited and heterogeneous evidence regarding the use of dynamic phototherapy and its various combined regimens for the management of actinic keratosis, there is a clear trend towards potential benefits compared to other therapies.